Contemporary prognosis of transient ischemic attack patients: A systematic review and meta-analysis. Issue 5 (July 2019) - Najib, Nashwa; Magin, Parker; Lasserson, Daniel; Quain, Debbie; Attia, John; Oldmeadow, Christopher; Garcia-Esperon, Carlos; Levi, Christopher
Background: Transient ischemic attacks are common and place patients at risk of subsequent stroke. The 2007 EXPRESS and SOS-TIA studies demonstrated the efficacy of rapid treatment initiation. We hypothesized that with these findings having informed subsequent transient ischemic attacks management protocols, transient ischemic attacks prognosis in contemporary (2008 and later) patient cohorts would be more favorable than in historical cohorts. Methods: A systematic review and meta-analysis of cohort studies and randomized control trial placebo-arms of transient ischemic attack (published 2008–2015). The primary outcome was stroke. Secondary outcomes were mortality, transient ischemic attack, and myocardial infarction. Studies were excluded if the outcome of transient ischemic attack patients was not reported separately. The systematic review included all studies of transient ischemic attack. The meta-analysis excluded studies of restricted transient ischemic attack patient types (e.g. only patients with atrial fibrillation). The pooled cumulative risks of stroke recurrence were estimated from study-specific estimates at 2, 7, 30, and 90 days post-transient ischemic attack, using a multivariate Bayesian model. Results: We included 47 studies in the systematic review and 40 studies in the meta-analysis. In the systematic review (191, 202 patients), stroke at 2 days was reported in 13/47 (27.7%) of studies, at 7 days in 20/47 (42.6%), at 30 days in 12/47 (25.5%), and at 90 days in 33/47 (70.2%). Studies included in the meta-analysis recruited 68, 563 patients. The cumulative risk of stroke was 1.2% (95% credible interval (CI) 0.6–2.2), 3.4% (95% CI 2.0–5.5), 5.0% (95% CI 2.9–8.9), and 7.4% (95% CI 4.3–12.4) at 2, 7, 30, and 90 days post-transient ischemic attack, respectively. Conclusion: In contemporary settings, transient ischemic attack prognosis is more favorable than reported in historical cohorts where a meta-analysis suggests stroke risk of 3.1% at two days.